Human Adenovirus Associated Hepatic Injury - Zheng, Nan; Wang, Yan; Rong, Hechen; Wang, Kun; Huang, Xiaoping (Frontiers in Public Health, 2022)
Human adenovirus (HAdV) is a common virus, but the infections it causes are relatively uncommon. At the same time, the methods for the detection of HAdV are varied, among which viral culture is still the gold standard. HAdV infection is usually self-limited but can also cause clinically symptomatic in lots of organs and tissues, of which human adenovirus pneumonia is the most common. In contrast, human adenovirus hepatitis is rarely reported. However, HAdV hepatitis has a high fatality rate once it occurs, especially in immunocompromised patients. Although human adenovirus hepatitis has some pathological and imaging features, its clinical symptoms are not typical. Therefore, HAdV hepatitis is not easy to be found in the clinic. There are kinds of treatments to treat this disease, but few are absolutely effective. In view of the above reasons, HAdV hepatitis is a disease that is difficult to be found in time. We reviewed and summarized the previously reported cases, hoping to bring some relatively common characteristics to clinicians, so as to facilitate early detection, early diagnosis, and early treatment of patients.